PyRAT: An Open-Source Python Library for Animal Behavior Analysis - De Almeida, Tulio Fernandes; Spinelli, Bruno Guedes; Hypolito Lima, Ramón; Gonzalez, Maria Carolina; Rodrigues, Abner Cardoso (Frontiers in Neuroscience, 2022)
Animal tracking softwares return a large amount of data and the available analytical tools are limited. Open access deep learning and computer vision emerged as prominent techniques to enhance speed and precision in visual data analysis. The aim of this study is to present a Python library toolbox (PyRAT - Python in Rodent Analysis and Tracking) capable to perform complex analysis of animal behavior. We used DeepLabCut to track 12 animals during exploration of an open field and an object exploration session. PyRAT is able to integrate electrophysiological signals with kinematic metrics, such as velocity, acceleration, presence in areas and object exploration. In addition, we developed an unsupervised algorithm to automatically extract and cluster distinct animal behavior. PyRAT's functions are available in an open access repository: https://github.com/pyratlib/pyrat.